THE ANALYSIS OF DIFFICULTIES IN WRITING NARRATIVE TEXT - Septha Muliani; Maida Norahmi; Natalina Asi (English Department of Faculty of Tarbiyah and Teacher Training, 2019)
The objective of this research was to analyze the difficulties in writing narrative text faced by the ninth grade students of SMP Negeri 11 Palangka Raya in the academic year 2018/2019 in using the generic structure and language features of the text. The research involved 20 students as the research participants. The method used in this research was descriptive research in which the research described and explained the actual data by conducting a writing test and analyzing the results. The results showed that 40% of the participants faced some difficulties in constructing the generic structure of the texts i.e. they failed in completing the generic structures of the texts and, mostly, missed one of the parts. Furthermore, there were 50% of the participants faced some difficulties in using the language features of narrative text, such as using past tenses, nouns, pronouns, verbal processes, and direct speech.